Efficiency of a Novel Multifunctional Corrosion Inhibitor Against Biofilms Developed on Carbon Steel - Tuck, Benjamin; Leinecker, Nadia; Watkin, Elizabeth; Somers, Anthony; Forsyth, Maria; Machuca, Laura L. (Frontiers in Bioengineering and Biotechnology, 2022)
In natural environments, populations of microorganisms rapidly colonise surfaces forming biofilms. These sessile communities comprise a variety of species which contribute to biofouling and microbiologically influenced corrosion (MIC), especially on metals. Species heterogeneity in natural systems confers higher tolerance to adverse conditions such as biocide treatment compared with single species laboratory simulations. Effective chemical treatments to combat recalcitrant biofilms are often dangerous to apply; both to operators and the environment, and face international embargoes. Today, there is a drive to exchange current toxic and environmentally hazardous biocides with less harmful compounds. One effective method of achieving this goal is to generate multi-functional compounds capable of tackling corrosion and biofilm formation simultaneously, thus reducing the number of compounds in dosing procedures. In a previous study, a novel corrosion inhibitor demonstrated biocidal effects against three marine isolates during the early stages of biofilm formation. The compound; CTA-4OHcinn, holds great promise as a multi-functional inhibitor, however its effect on complex, multi-species biofilms remains unknown. Here we evaluate CTA-4OHcinn biocidal capacity against multi-species biofilms developed from oilfield samples. Mature biofilms were developed and treated with 10 mM CTA-4OHcinn for 4 h. The effects of the compound were assessed using mean probable number (MPN), adenosine triphosphate (ATP) quantification, scanning electron microscopy (SEM) and confocal laser scanning microscopy (CLSM). Results demonstrate that CTA-4OHcinn significantly reduces the viability of mature biofilms, supporting previous demonstrations on the secondary function of CTA-4OHcinn as a biocide. CLSM results further indicate that CTA-4OHcinn targets the cell membrane resulting in lysis. This finding complements the established corrosion inhibition function of CTA-4OHcinn, indicating the compound is a true multi-functional organic corrosion inhibitor.